Random Mutagenesis by Whole-Plasmid PCR Amplification. (March 1998) - Parikh, Asit; Peter Guengerich, F.
Random mutagenesis has become a powerful means of studying the effects of a large number of permutations of a particular DNA sequence. As a prime example, libraries of randomized cDNA clones, when translated into their corresponding proteins, can be useful in investigating the functional contributions of a mutagenized region to the overall properties of a protein. Existing molecular cloning techniques for random mutagenesis are tedious and frequently plagued with high levels of background from wild-type (nonmutagenized) template. We report a PCR-based method involving amplification of an entire plasmid containing a gene sequence of interest with partially complementary degenerate oligonucleotides for randomization of up to 12 consecutive nucleotide residues. Sequential treatment of the PCR product with Dpn I and a second specific restriction endonuclease and T4 DNA ligase followed by high-efficiency electroporation permits the generation of libraries with very low background. This technique should prove useful for studies on enzyme structure-function relationships as well as for other diverse applications.